EXTENSION TEKTONIK SELAT SUNDA - -, Budi Mulyana (Bulletin of Scientific Contribution, 2006)
Sumatra and Java Islands are representing a part of Sunda arc from plate of southern Eurasia. It started from north Andaman sea of Aceh-Sumatra-Jawa to southern Sumbawa island. Its network is including into island arc systems with mechanism of subduksi between Indo-Australian to Eurasia plates. Change of direction and speed of Indo-Australia plate subduction to Eurasia plate is started normally in part of Southern Java - Java Trench - becoming subduction oblique at Sumatra Trench. Change of the pattern cause to be formed its Fault Sumatra System (Fault of Semangko and Fault laugh) at Sumatra Island tinder, mark with lines Sunda strait volkanic area start from eldest of Sukadana, Krakatau Compleks to Panaitan young island. Change pattern direction of speed and movement of Indo-Australia plates to Eurasia plates is very interconnected sliver with effect of movement of India plate of collision the India continent.